The proprietary consequences of foreign marriages for the purposes of estate planning and succession in South Africa - Thorne, Aimee Liza (Rhodes University, Faculty of Law, Law)
This thesis is intended to provide clarity regarding the proprietary consequences of foreign marriages in the context of estate planning and succession in South Africa. It includes an exploration into the impact of specific legislation on foreign marriages, the implications of matrimonial property regimes on a deceased estate in South Africa, private international law principles affecting matrimonial property and succession claims, the scope of antenuptial contracts and postnuptial contracts as existing remedies for foreign remedies, and the harmonisation of succession and matrimonial property law in the European Union (EU). It furthermore suggests potential reforms for the overhaul of the lex domicilii matrimonii principle and associated issues arising therefrom. Various specific issues discussed include the waiver of accrual claims, maintenance claims by surviving spouses of a foreign marriage, choice-of-law rules for matrimonial property rights and succession rights, the registration of a domestic or foreign antenuptial contract for foreign marriages, the formal validity and proper law of antenuptial contracts, the operation of the immutability principle on a domestic and international level, and the common-law approach to the recognition of postnuptial contracts and spousal donations.
Keywords: Marital property -- South Africa; South Africa. Matrimonial Property Act 1984; Conflict of laws Marital property; Estates (Law) -- South Africa; Inheritance; Prenuptial agreements -- South Africa; Postnuptial agreements -- South Africa